2015
DOI: 10.1002/admi.201500203
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasensitive and Fast Moisture Sensor Based on Self‐Assembled Dopamine–Melanin Thin Films

Abstract: biomacromolecule remains a challenge. [ 11 ] Diffi culties associated with the extraction of natural melanin have inspired the development of synthetic melanin, [ 12 ] which can mimic the properties of natural melanin, including its hydrationdependent conducting behavior. For example, the conductivity of 1 mm thick 3,4-dihydroxyphenylalanine (DOPA) melanin pellets was found to be 10 −13 S cm −1 at relative humidity (RH) of 0% and 10 −5 S cm −1 at 100% RH, an eight order of magnitude difference. [ 13 ] Thin fi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…The reaction in Figure is a simple manifestation of Le Chatelier's principle with the addition of water driving hydronium and SQ formation, and long range proton transport occurring above a matrix percolation threshold. This process leads to orders of magnitude change in the conductivity of melanin as a function of water content . It is interesting to speculate whether the mechanism is generic amongst other biomacromolecules that support electrical currents such as proteins or polysaccharides .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction in Figure is a simple manifestation of Le Chatelier's principle with the addition of water driving hydronium and SQ formation, and long range proton transport occurring above a matrix percolation threshold. This process leads to orders of magnitude change in the conductivity of melanin as a function of water content . It is interesting to speculate whether the mechanism is generic amongst other biomacromolecules that support electrical currents such as proteins or polysaccharides .…”
Section: Introductionmentioning
confidence: 99%
“…Other nucleophilic buffer components such as ammonia and primary amines have similar effects on polymerization as Tris, leading to generally similar material properties and the small variations between nucleophilic buffers have been used to tune the ultimate aggregate properties. For example, ammonia is used to control particle size in solution and aniline has been used to suppress particle formation in the formation of polydopamine thin films at the air–water interface . Further, the changing polymerization processes in nucleophilic and nonnucleophilic buffers have specifically been exploited, with dopamine deposited from phosphate buffer and then from Tris to increase surface roughness of the coating for a superhydrophobic surface …”
Section: Catecholamine Polymers: Chemistry and Structurementioning
confidence: 99%
“…Early work with natural melanins suggested that they had semiconductor properties . However, based on the hydration dependence of those properties, more recent research shows that the melanin structure is best described as a hybrid ionic–electronic conductor in which both electrons and protons released by comproportionation are involved in electrical conduction ( Figure ) . Polydopamine exhibits the same hybrid ionic–electronic conductivity as natural eumelanins, which has already been exploited variously and provides great potential for use in bioelectronic devices that are capable of integration with living tissue …”
Section: Catecholamine Polymers: Chemistry and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The formation of free-standing polydopamine (PDA) lms has attracted great attention recently. [1][2][3][4][5][6][7][8][9] PDA lms show different colours modulated by the polymerization conditions, 3 and they can be transferred to various substrates to form functional coatings. A promising humidity sensor with quick response and recovery time was developed based on PDA lms.…”
Section: Introductionmentioning
confidence: 99%